Upaya dan kontribusi mahasiswa penerima beasiswa terhadap negara Indonesia: Studi kasus mahasiswa angkatan 22 UIN Maulana Malik Ibrahim Malang - Dzikrullooh, Rahmania Ramadhani (Maliki Interdisciplinary Journal, 2023)
A B S T R A C T The role of students who are currently often highlighted by the community, where students are agents of the nation’s successor who will provide every beneficial change to the nation and state of Indonesia, is often found some students who receive education free of charge, but through scholarships obtained, both scholarships from state and private governments. No less than regular non-scholarship students, these scholarship recipients have a strong spirit and great hope to contribute to Indonesia. This is in line with the relationship between the state and citizens. Students as scholarship recipients must be able to give back to the state as a form of gratitude for the cost of education they receive. The purpose of this study is to find out more about the relationship between the state and citizens in the context of scholarships This research is a type of qualitative research by conducting a case study method. The data collection techniques used in this research are observation and interviews by going directly to the field to get case details on scholarship recipient students at UIN Maulana Malik Ibrahim Malang class 22.